Can myocardial dysfunction be detected in patients with rheumatoid arthritis with no cardiac symptoms? - Akgol, G.; Gulkesen, A.; Uslu, E. Y.; Alkan, G.; Bolayir, H. A.; Gelen, M. A.; Uslu, M. F. (Verduci Publisher, 2023)
OBJECTIVE: The aim of our study was to investigate the role of tissue Dop-pler and Myocardial Performance Index (MPI) in evaluating cardiac involvement in patients with rheumatoid arthritis (RA) with no cardi-ac symptoms, to determine whether these mea-surements differ between healthy controls and RA patients, and whether they can be used to determine the risk of cardiovascular disease and predict prognosis.PATIENTS AND METHODS: 50 RA patients fulfilling the 2010 American College of Rheuma-tology/European League Against Rheumatism (ACR/EULAR) RA criteria and 50 healthy volun-teering controls were included in the study. All patients and controls were assessed using elec-trocardiography (ECG), echocardiography, con-ventional Doppler echocardiography and tissue Doppler echocardiography. MPI values were cal-culated. In addition, RA patients were compared after being divided into two subgroups: sero-positive and seronegative RA. Disease activi-ty levels of the patients were determined based on Disease Activity Score in 28 Joints (DAS28).RESULTS: The control group and RA group were compared in terms of PR interval, left atrial diameter, E/A, E/e', and MPI values. Comparisons between the groups yielded statistically signifi-cant differences in left atrial diameter, E/A, E/e', and MPI values and no significant difference in PR intervals. These parameters were also com-pared between seropositive and seronegative pa-tients. Left atrial diameter was significantly high-er in seronegative patients than in seropositive patients. There was no significant difference in the other values. DAS28 scores had no correla-tion with cardiac parameters.CONCLUSIONS: Early detection of ventricu-lar dysfunction in RA may be useful in clinical practice when predicting prognosis and optimiz-ing treatment. The present study found that RA patients had impaired tissue Doppler measure-ments and MPI results compared to controls. MPI and tissue Doppler may be useful in early detection of ventricular dysfunction.
Keywords: Rheumatoid arthritis; Myocardial performance in-dex (MPI); Tissue doppler